2017
DOI: 10.1021/acs.joc.7b00741
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Functionalizations of C60 with Amino Alcohols

Abstract: CuI-catalyzed diverse functionalizations of C with amino alcohols with aerobic oxygen as the sole oxidant have been explored. For 2-/3-amino alcohols, an aminooxygenation reaction occurs to generate fulleromorpholine and fullerooxazepane derivatives. When a tethered furan ring exists, a further intramolecular [4 + 2] reaction with the neighboring double bond occurs to furnish the cis-1 products. In the case of 4-/5-amino alcohols, methanofullerenes linking with cyclic amides are obtained through cyclic enamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In this respect, our group has recently managed the addition of an N-centered radical to C 60 , which has been attracting less attention compared to the C/O-radical. By using the iodine/I 2 system or Cu­(I/II) reagents, a variety of nitrogen-containing heterocycle-fused C 60 derivatives have been obtained via the respective reaction of C 60 with amines/amides/amidines/sulfonamides/sulfamides/ureas.…”
Section: Introductionmentioning
confidence: 73%
“…In this respect, our group has recently managed the addition of an N-centered radical to C 60 , which has been attracting less attention compared to the C/O-radical. By using the iodine/I 2 system or Cu­(I/II) reagents, a variety of nitrogen-containing heterocycle-fused C 60 derivatives have been obtained via the respective reaction of C 60 with amines/amides/amidines/sulfonamides/sulfamides/ureas.…”
Section: Introductionmentioning
confidence: 73%
“…This signal confirmed that fullerenyl radicals or radical cations are generated in the present coupling reaction. Additionally, when 3 equiv of butylated hydroxytoluene was added as a radical scavenger, the coupling reaction was completely suppressed, and the starting RC 60 H was completely recovered (Figure S23), which also confirmed that a radical process is involved in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We modeled the interaction of approximately 1 kpc cores in two galactic centers (see Section 2.1.2), assuming that the mass accretion toward the galactic nuclei is dominated by dense gas in the galactic central region. This ensures better spatial (4 pc) and SPH mass (1000 M e ) resolutions than previous gas-rich major merger simulations (for example, Narayanan et al 2010;Blecha et al 2018;Yang et al 2021). 8 The formation and evolution of the merger system were studied by postprocessed pseudo-observations using the radiation transfer simulation code RADMC-3D (Dullemond et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Blecha et al (2018) studied the evolution of gasrich merger systems using the N-body/smoothed particle hydrodynamics (SPH) code GADGET-3 with a spatial resolution of 23-48 pc and a mass resolution of 2.8 × 10 5 M e . More recently, Yang et al (2021) performed similar simulations for less massive galaxies with smaller BHs (1.5-3 × 10 6 M e ) using GADGET-2 with spatial resolutions and masses of 20 pc and 4.6 × 10 3 M e , respectively. The geometry and internal distribution of the gas and dust in r < 100 pc are crucial for the multiwavelength observational properties of AGNs (Schartmann et al 2014;Wada et al 2016;Izumi et al 2018).…”
Section: Introductionmentioning
confidence: 99%